2003
DOI: 10.1002/ps.819
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal activity of the enantiomers of fipronil

Abstract: The two enantiomers of the insecticide fipronil were made by preparative HPLC. The insecticidal activities of the racemic mixture and the two enantiomers against selected agricultural or household pests (cotton stainer, Dysdercus cingulatus F; grain weevil, Sitophilus granarius L and house fly, Musca domestica L) were determined. There was no significant difference in acute or residual activity between the racemic mixture and the enantiomers of fipronil, indicating that there is no preferred chiral form of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 5 publications
1
28
0
1
Order By: Relevance
“…Fipronil enantiomers were separated using a Jasco LC-2000 series HPLC system (Jasco, Japan) according to an established method 21 . The resolved fractions were manually collected at the HPLC outlet, evaporated until dry, and dissolved in ethanol.…”
Section: Methodsmentioning
confidence: 99%
“…Fipronil enantiomers were separated using a Jasco LC-2000 series HPLC system (Jasco, Japan) according to an established method 21 . The resolved fractions were manually collected at the HPLC outlet, evaporated until dry, and dissolved in ethanol.…”
Section: Methodsmentioning
confidence: 99%
“…26,27 In addition, the α,β configuration of the glucosyl group also exists. Their configurations were confirmed on the basis of a chemical shift, coupling constants, and band shape of H-1.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…There have been four studies, including the present study, that examined toxicities of fipronil enantiomers to 11 species [21][22][23]. In these 11 species, only two species (Procambarus clarkii and Ceriodaphnia dubia) demonstrated enantioselectivity in toxicities [22,23].…”
Section: Toxicitiesmentioning
confidence: 96%
“…There are a number of investigations on enantiomer-specific toxicity of fipronil in the literature. Teicher et al [21] observed no significant difference in toxicity of fipronil and its enantiomers to three agricultural and household pests (cotton stainer, Dysdercus cingulatus; grain weevil, Sitophilus granarius; house fly, Musca domestica L.). In contrast, Konwick et al [22] demonstrated the S(þ)-enantiomer was significantly more toxic to Ceriodaphnia dubia than either the R(À)-enantiomer or racemate.…”
Section: Introductionmentioning
confidence: 98%